The Economic purpose development of public open space and ecological disruption: A case study with the special reference with Crow Island beach park in Colombo - Rewathy, K.; Hafsa, M.N.F. (South Eastern University of Sri Lanka, 2019)
The world constantly moving towards its new expeditions, inventions and development. In the process of rapid development each and every country loses its concentration in natural and urban open spaces where multiple lives survive on the earth rather than humans. Public urban open spaces such as wetland, mangrove forest, beaches and parks are often being target on the thought of tourism development and urban development. Despite the economic gain for the country, there are multiple problems arising to the ecology due to the lack of maintenance and proper waste disposal management. The overall aim of this paper is to analysis economic and social well-being of Crow Island beach park development and investigate the ecological disruption and biodiversity collapse. Most of the economic benefits and social development has been analyzed with a questionnaire survey and unstructured interviews as well as the ecological disruption has been investigated on a field observation and published articles, reports and maps. With the analysis of the primary and secondary data, the results summarizes the both sides of the public urban open space development. The beach park duly becoming unattractive due to its lack of management and waste dumping. Most of the areas in the park abandoned by the visitors because of its uncleanliness. Proper environment management of the park could benefit to both economy and preservation of biodiversity. The sustainable development of any natural phenomenon could give its fruitfulness to both human and environment. Keywords: Biodiversity, Crow Island, Development, Economy, Open space